Safety and Localization of Mesenchymal Stromal Cells Derived from Human Adipose Tissue-Associated Hyaluronic Acid: A Preclinical Study - Janaína José dos Santos Machado; Bernard Gomes Piñeiro; Isalira Peroba Ramos; Sergio Augusto Lopes de Souza; Bianca Gutfilen; Maria Helena Nicola; Paulo Roberto Cotrim de Souza; Eduardo Cruz; Regina Coeli Goldenberg (Stem Cells International)
Millions of plastic surgeries are performed worldwide every year with the objective of correcting lipodystrophies stemming from lesions, tumor resections, birth defects, and AIDS-associated antiretroviral therapy. Besides that, a large number of clinical research have assessed the outcome of procedures that rely on combinations of dermal fillers and autologous cells. However, little is known about the safety of these combinations and the localization of the injected cells. The aim of this study was to test the toxicity of a solution containing 1% hyaluronic acid (HA) and adipose-derived stromal cells (ASCs) from the human adipose tissue and to assess the localization of the injected cells, with and without HA, labeled with technetium-99m. Rats received subcutaneous and intraperitoneal injections of a solution containing 1% HA/adipose-derived stromal cells isolated from the human fat tissue. The animals were then observed for up to forty-two days. The solution tested in this study did not result in systemic, biochemical, or anatomic alterations that could represent toxicity symptoms. The association of HA and ASCs labeled with technetium-99m remained at the site of the injection within a period of twenty-four hours, as demonstrated by a whole-body imaging software fusion of SPECT and CT. In conclusion, our study shows that the subcutaneous and intraperitoneal injection of HA associated with adipose-derived stromal cells (ASCs) is safe. The association of HA and ASCs did not induce local or systemic toxicity. Thus, the administration of volume equal to or less than 0.2 mL of the agent filler (1×106 ASC+HA 1%) should be considered for subsequent studies and may be an alternative to dermal fillers due to the expected lasting effects.